Penerapan Manajemen Konflik Berbasis Agama Dan Psikologi: Studi Kasus di SMK Negeri 29 Jakarta - Valentina Purnama Dewi; Sugeng Suwagi; Udin Sumarsah (Eduvis : Jurnal Manajemen Pendidikan Islam, 2021)
This journal aims to identify forms of conflict in schools, to find out how school principals solve problems or conflicts using conflict management. This study uses a qualitative approach and case study methods. Techniques in data collection: using document searches, archives, interviews, and participant observation. Interviews were conducted with school principals, vice principals, teachers, and among students. Direct observations were made to explore conflict management in schools. The results of the study: (1) conflicts that occur between students, individuals or groups can take the form of bullying, fights or brawls. (2) conflicts that occur between students are caused by differences in perceptions, goals and dependencies between them. (3) conflicts between students and teachers take the form of disrespectful attitudes, ignoring lessons, physical threats to teachers. (4) conflict between teachers - students, due to the unpreparedness of teachers to accept criticism, as well as unequal perceptions and goals, as well as unpreparedness of teachers in learning (5) schools resolve conflicts by: bringing in characters, creating new conflicts, implementing school programs to build commitment, open communication and intimacy with each other. (6) to resolve conflicts, teachers must build communication & intimacy with students, facilitating the resolution of conflicts between them. The religious approach is carried out by making a schedule for memorizing short verses during morning apples and tadarus every Tuesday and Thursday, and a psychological approach by telling famous figures and their life problems and diverting extra students' energy to useful activities such as extracurricular activities and farming around the school. ABSTRAK Jurnal ini bertujuan, mengenali bentuk konflik di sekolah, mengetahui bagaimana kepala sekolah menyelesaikan masalah atau konflik dengan menggunakan manajemen konflik. Penelitian ini menggunakan pendekatan kualitatif dan metode studi kasus. Teknik dalam pengumpulan data: menggunakan penelusuran dokumen, arsip, wawancara, dan observasi partisipan. Wawancara dilakukan dengan kepala sekolah, wakil kepala sekolah, guru-guru, dan antar siswa. Pengamatan langsung dilakukan untuk mendalami manajemen konflik di sekolah. Hasil penelitian: (1) konflik yang terjadi diantara para peserta didik, individu atau kelompok bisa berwujud bullying, perkelahian atau tawuran. (2) konflik yang terjadi antara peserta didik disebabkan perbedaan persepsi, tujuan dan ketergantungan antara mereka. (3) konflik antara peserta didik dengan guru berwujud sikap tidak sopan, mengabaikan pelajaran, ancaman fisik terhadap guru. (4) konflik antara guru - peserta didik, karena ketidaksiapan guru menerima sikap kritik, serta ketidaksamaan persepsi dan tujuan, serta ketidak siapan guru dalam pembelajaran (5) sekolah menyelesaikan konflik dengan cara: mendatangkan tokoh, menciptakan konflik baru, penerapan progam-program sekolah untuk membangun komitmen, komunikasi yang terbuka dan keakraban satu sama lain. (6) untuk menyelesaikan konflik, guru harus membangun komunikasi & keakraban dengan peserta didik, memudahkan penyelesaian konflik diantara mereka. Pendekatan secara agama dilakukan dnegan membuat jadwal hafalan ayat pendek saat apel pagi dan tadarus setiap hari selasa kamis, dan pendekatan secara psikologis dengan menceritakan tokoh-tokoh terkenal dan kendala hidup mereka serta mengalihkan tenaga ekstra siswa kepada kegiatan yang bermanfaat seperti ekstrakurikuler dan bertani disekitar sekolah.